Compressive strength of manganese fine-grained material and molasses briquettes regarding binder content and curing time - Rondon Gonçalves, Dhaffiny; Gustavo Mendes de Jesus, Leandro (International Journal of Scientific World, 2024)
In the production of raw materials for the manufacture of ferroalloys, up to 50% of the material mined is discarded as fine-grained tailings. Those tailings are deposited in dams, which are considered an environmental liability. To avoid this, an alternative would be to agglomerate the tailing dam materials using the briquetting process. Therefore, this work aims to evaluate the compressive strength of briquettes made of manganese fine-grained material (with particle size < 2.00 mm) and molasses regarding curing time and percentage of binder. To achieve the objective, 45 briquettes were made with fine-grained manganese ore, with 3 different molasses content (binder), these were put into 3 weeks of curing, to analyze the impact of binder content and curing time. The result was that the longer the curing time, the better the compressive strength and that increasing binder content reduces its compressive strength. Finally, the best results were obtained with 5 % binder and 3 weeks of curing time, in which the agglomerate produced had a compressive strength of 9,0 MPa.